ORIENTALISM AND CULTURAL HEGEMONY IN SEXY BY JHUMPA LAHIRI: A POSTCOLONIALISM APPROACH - Rahmadina Vita Jannah; Dyah Uyun Wulandari; Qirara; Ima Dyah Savitri; Jiphie Gilia Indriyani; Shabrina An Adzhani (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This paper examines the themes of orientalism and cultural hegemony in Jhumpa Lahiri’s short story Sexy through the lens of postcolonial theory, particularly Edward Said’s concept of Orientalism and Gramsci’s hegemony. The narrative explores the dynamics between Miranda, a white American woman, and Dev, a married Indian man, highlighting the fetishization of Eastern culture and the alienation faced by diasporic individuals. Lahiri portrays how the West's portrayal of the East as exotic and "other" perpetuates stereotypes, while cultural hegemony underscores the dominance of Western ideologies in shaping global standards of beauty and identity. Through Miranda’s curiosity about Indian culture and her fascination with Dev’s heritage, the story reveals how colonial legacies continue to influence perceptions and relationships. The paper argues that Lahiri’s critique in Sexy illuminates the complexities of cultural identity and power imbalance, urging readers to reconsider entrenched biases and the lingering impacts of postcolonialism.